Selection of Pavement Types on Village Roads in Bojonegoro Regency - Heri Cahyono Putra; Budi Yulianto; Ary Setyawan (Bentang : Jurnal Teoritis dan Terapan Bidang Rekayasa Sipil, 2024)
Bojonegoro Regency village road infrastructure development continues to be carried out through Special Financial Assistance. The choice of flexible pavement and rigid pavement types used in local construction has different characteristics, advantages and disadvantages. This comparison of pavement is relevant to the quality and cost of road maintenance. The research was conducted to analyze and assess the condition of village roads in Bojonegoro Regency by analyzing cost efficiency and analyzing the type of construction that suits village road needs, using the PCI (Pavement Condition Index) method to assess the condition of road sections and remaining service life. Samples were taken at 3 locations with results from Glagahwangi Village, Sugihwaras District, 77.33 (very good) with a repair cost of IDR 32,458,293 and remaining service life of 9.25 years, Sukowati Village, Kapas District 71.8 (very good) with repair costs IDR 34,501,280 and remaining service life of 7.44 years, and Pekuwon Village, Sumberejo District 78 (good) with repair costs of IDR 23,753,750 and remaining service life of 9.33 years. Pekuwon Village has the best efficiency of IDR 2,545,953,- per year compared to other village road pavement models.